MLC positional accuracy evaluation through the Picket Fence test on EBT2 films and a 3D volumetric phantom. (8th March 2015) - Antypas, Christos; Floros, Ioannis; Rouchota, Maritina; Armpilia, Christina; Lyra, Maria
Abstract : The accuracy of MLC positions during radiotherapy is important as even small positional deviations can translate into considerable dose delivery errors. This becomes crucial when radiosensitive organs are located near the treated volume and especially during IMRT, where dose gradients are steep. A test commonly conducted to measure the positional accuracy of the MLCs is the Picket Fence test. In this study two alterations of the Picket Fence test were performed and evaluated, the first one using radiochromic EBT2 films and the second one the Delta 4 PT diode array phantom and its software. Our results showed that EBT2 films provide a relatively fast, qualitative visual inspection of the significant leaf dispositions. When slight inaccuracies need to be revealed or precise numerical results for each leaf position are needed, Delta 4 PT provides the desired accuracy of 1 mm. In treatment modalities where a higher accuracy is required in the delivered dose distribution, such as in IMRT, precise numerical values of the measurements for the MLC positional inspection are required. PACS number: 87.55.Qr, 87.56.bd, 87.56.Fc, 87.56.nk